Effects of different types of warm-up on swimming performance, reaction time, and dive distance - Balilionis, G.; Nepocatych, S.; Ellis, C. M.; Richardson, M. T. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to evaluate the effects of 3 types of warm-up (WU) on swimming performance, reaction time, and dive distance. In repeated-measures counterbalanced design, National Collegiate Athletic Association Division I swimmers (n = 16) used 3 WUs before performing 50-yd (45.7-m) freestyle swim trials. The WU consisted of (a) no WU, (b) short WU (50-yd at 40% of swimmers' maximal effort and 50-yd at 90%), and (c) regular WU (usual precompetition WU). The mean 50-yd time was significantly faster (p = 0.01) after the regular WU (24.95 ± 1.53 seconds) when compared with that of the short WU (25.26 ± 1.61 seconds). However, individual data indicated that 19% of the participants performed their best in the 50-yd category after short, 37% after no, and 44% after regular WU. Heart rate was significantly higher (p = 0.01) after regular WU (100 ± 13 b/min) when compared with that of the no WU category (88 ± 18 b/min). However, no significant differences among WUs were found for reaction time (p = 0.96), rating of perceived exertion post 50-yd time trial (p = 0.11), dive distance (p = 0.67), or stroke count (p = 0.23). In conclusion, the average regular WU was better than short or no WU to achieve the fastest mean time in the 50-yd freestyle; however, some individual performances were faster after WUs different from their regular approach.